2022
DOI: 10.1177/09544089221081339
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Viscous dissipation and thermal radiation impact on MHD mass transfer natural convective flow over a stretching sheet

Abstract: Impact of viscous dissipation and radiation on MHD free convective mass transfer of an incompressible, viscous fluid flow through a stretching surface is examined. By applying similarity variables, the governing non-linear PDE's are converted into nonlinear ODEs. Keller-Box approach gets numerical solutions to these equations. The effect of non-dimensional variables is studied and graphically illustrated on velocity, temperature, and concentration. It is observed that the growth in the chemical reaction parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Khan et al 45 examined Carreau fluid surface with variable thickness using Keller Box method. Nalivale et al 46 studied natural convective flow with viscous dissipation and thermal radiation effects. Megahed et al 47 described Carreau fluid with heat flux and variable thermal conductivity under thermal radiation impact.…”
Section: List Of Symbols U Vmentioning
confidence: 99%
“…Khan et al 45 examined Carreau fluid surface with variable thickness using Keller Box method. Nalivale et al 46 studied natural convective flow with viscous dissipation and thermal radiation effects. Megahed et al 47 described Carreau fluid with heat flux and variable thermal conductivity under thermal radiation impact.…”
Section: List Of Symbols U Vmentioning
confidence: 99%
“…Based on their analysis, Hayat et al [20] concluded that the temperature difference parameter and the radiation parameter are what really make the thermal panel shine when it comes to the flow of Oldroyd-B fluid powered by a heated stretched sheet. The impacts of viscous fluid flow upon stretching geometry and the repercussions of thermal radiation were proposed by Nalivela et al [21]. They deduced that as the radiation parameter grew larger, the temperature profile increased.…”
Section: Introductionmentioning
confidence: 98%
“…The impacts of viscous fluid flow upon stretching geometry and the repercussions of thermal radiation were proposed by Nalivela et al. [21]. They deduced that as the radiation parameter grew larger, the temperature profile increased.…”
Section: Introductionmentioning
confidence: 99%
“…Mabood et al (2022) inspected the influence of the non-linearly radiated 3D time-based MHD hybrid nanofluid flow. Readers can further study about the impact of MHD on mass and heat transmission in Sulochana et al (2018), Alshehri et al (2021), Mabood et al (2021), Bejawada et al (2022), Nalivela et al (2022).…”
Section: Introductionmentioning
confidence: 99%